CD8+ T Cell Response to Gammaherpesvirus Infection Mediates Inflammation and Fibrosis in Interferon Gamma Receptor-Deficient Mice. - Brigid M O'Flaherty; Caline G Matar; Brian S Wakeman; AnaPatricia Garcia; Carol A Wilke; Cynthia L Courtney; Bethany B Moore; Samuel H Speck (PLoS ONE, 2015)
Idiopathic pulmonary fibrosis (IPF), one of the most severe interstitial lung diseases, is a progressive fibrotic disorder of unknown etiology. However, there is growing appreciation for the role of viral infection in disease induction and/or progression. A small animal model of multi-organ fibrosis, which involves murine gammaherpesvirus (MHV68) infection of interferon gamma receptor deficient (IFNγR-/-) mice, has been utilized to model the association of gammaherpesvirus infections and lung fibrosis. Notably, several MHV68 mutants which fail to induce fibrosis have been identified. Our current study aimed to better define the role of the unique MHV68 gene, M1, in development of pulmonary fibrosis. We have previously shown that the M1 gene encodes a secreted protein which possesses superantigen-like function to drive the expansion and activation of Vβ4+ CD8+ T cells. Here we show that M1-dependent fibrosis is correlated with heightened levels of inflammation in the lung. We observe an M1-dependent cellular infiltrate of innate immune cells with most striking differences at 28 days-post infection. Furthermore, in the absence of M1 protein expression we observed reduced CD8+ T cells and MHV68 epitope specific CD8+ T cells to the lungs-despite equivalent levels of viral replication between M1 null and wild type MHV68. Notably, backcrossing the IFNγR-/- onto the Balb/c background, which has previously been shown to exhibit weak MHV68-driven Vβ4+ CD8+ T cell expansion, eliminated MHV68-induced fibrosis-further implicating the activated Vβ4+ CD8+ T cell population in the induction of fibrosis. We further addressed the role that CD8+ T cells play in the induction of fibrosis by depleting CD8+ T cells, which protected the mice from fibrotic disease. Taken together these findings are consistent with the hypothesized role of Vβ4+ CD8+ T cells as mediators of fibrotic disease in IFNγR-/- mice.